Calpain: the regulatory point of myocardial ischemia-reperfusion injury - Liu, Guo-Yang; Xie, Wan-Li; Wang, Yan-Ting; Chen, Lu; Xu, Zhen-Zhen; Lv, Yong; Wu, Qing-Ping (Frontiers in Cardiovascular Medicine, 2023)
Calpain is a conserved cysteine protease readily expressed in several mammalian tissues, which is usually activated by Ca2+ and with maximum activity at neutral pH. The activity of calpain is tightly regulated because its aberrant activation will nonspecifically cleave various proteins in cells. Abnormally elevation of Ca2+ promotes the abnormal activation of calpain during myocardial ischemia-reperfusion, resulting in myocardial injury and cardiac dysfunction. In this paper, we mainly reviewed the effects of calpain in various programmed cell death (such as apoptosis, mitochondrial-mediated necrosis, autophagy-dependent cell death, and parthanatos) in myocardial ischemia-reperfusion. In addition, we also discussed the abnormal activation of calpain during myocardial ischemia-reperfusion, the effect of calpain on myocardial repair, and the possible future research directions of calpain.